2002
DOI: 10.1021/jp0208844
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the NCN Radical

Abstract: Reactions Reactions H 1000Kinetics of the NCN Radical. -The kinetics of the reaction of NCN with NO are monitored using laser-induced fluorescence spectroscopy over the temperature range 298-573 K. The reaction proceeds primarily through NCNNO adduct formation as evidenced by significant pressure dependence of the rate constant. The reaction displays a negative temperature dependence typical of radical-radical reactions. Only very small amounts of N 2 O products are detected. Upper limits for the low-pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 45 publications
7
39
1
Order By: Relevance
“…The outdated, several orders of magnitude higher rate constant estimate from Glarborg et al [13] is not shown. The reported upper limit by Baren and Hershberger (dotted curve) [12], which was based on low-temperature (298-573 K) and lowpressure (ß3 Torr) experiments is not directly comparable with our data but does not contradict our results. The overall agreement with the transition state calculations is rather satisfying.…”
Section: Ncn + Ocontrasting
confidence: 95%
See 1 more Smart Citation
“…The outdated, several orders of magnitude higher rate constant estimate from Glarborg et al [13] is not shown. The reported upper limit by Baren and Hershberger (dotted curve) [12], which was based on low-temperature (298-573 K) and lowpressure (ß3 Torr) experiments is not directly comparable with our data but does not contradict our results. The overall agreement with the transition state calculations is rather satisfying.…”
Section: Ncn + Ocontrasting
confidence: 95%
“…for temperatures between 298 and 573 K [12]. In a first attempt to compile a high-temperature NCN mechanism for NO x formation, Glarborg et al estimated a value of k 2 = 1.0 × 10 13 cm 3 mol −1 s −1 [13].…”
Section: Introductionmentioning
confidence: 99%
“…At shorter photolysis wavelengths, also 1 NCN was formed, and a first-order relaxation time of 0.5 ms for 1 NCN was obtained and attributed to phosphorescence [29]. Baren and Hershberger [30] studied the NCN + NO reaction in the gas phase by time-resolved detection of 3 NCN with laser-induced fluorescence (LIF) at 329.008 nm. These authors observed delayed rise times of the 3 NCN fluorescence signals on the order of 15 μs that were attributed to the mechanism of NCN formation via photolysis of CH 2 N 2 /C 2 N 2 mixtures.…”
Section: Ncnmentioning
confidence: 99%
“…Meanwhile, reaction (1b) has been experimentally proven to be the main product channel of reaction (1) [6][7][8][9][10]. Simultaneously, experimental work on NCN reactions has been carried out [11][12][13][14][15][16][17]. Besides the photolysis of diazomethane (CH 2 N 2 ) in the presence of cyanogen (C 2 N 2 ), the photolysis or pyrolysis of NCN 3 served as a source of NCN radicals.…”
Section: Introductionmentioning
confidence: 99%